Composition-controlled synthesis and tunable optical properties of ternary boron carbonitride nanotubes. Issue 21 (21st February 2017) - Li, Hongling; Tay, Roland Yingjie; Tsang, Siu Hon; Jing, Lin; Zhu, Minmin; Leong, Fei Ni; Teo, Edwin Hang Tong
Abstract : Ternary boron nitride nanotubes (BCNNTs) with controllable compositions and tunable optical band gaps have been successfully achieved. Abstract : Controlling the composition and structure of boron carbonitride nanotubes (BCNNTs) is the critical factor for tuning their electrical and optical properties, which in turn allows for the broadening of their applications. However, most of the known methods for synthesizing BCNNTs employ toxic precursors at high temperatures (up to 2000 °C) and the achieved BCNNTs usually encounter phase-separation of BN and C. Herein, a facile large-scale synthesis of ternary BCNNTs with controllable composition by a chemical vapor deposition process at a relatively low temperature of 900 °C is reported. By simply adjusting the synthetic parameters, BCNNTs with two different atomic ratios of B : C : N can be successfully synthesized. Their morphologies and ternary structure as well as optical properties are further investigated. Notably, the as-prepared BNCNTs-50 are stable up to 900 °C in air and exhibit an optical band gap of ∼4.36 eV. The results demonstrated in this study will open new avenues for a variety of potential applications of BCNNTs in electronics, photonics, sensors and high temperature lubricants.